EuroREGEN - A Participatory Action Research agenda for knowledge production and coalition-building - Esteves, A. (GEN Research Colloquium Series, 2021)
How CLIs construct themselves as economic actors Structural conditions in which particular frames, structures of governance and resource mobilization strategies gain force: Processes of institutional legitimation: In every society, multiple norms and values exist, which are conveyed in the forms of competing narratives. While some remain societally marginalized, others become hegemonic (Leach et al 2010) and powerfully shape production and consumption processes (Beckert 2013). “Semiotic structures (frames) combine with distinctive institutional dynamics to marginalize alternative stories” (Polletta 2006: 15). Agency of “movement entrepreneurs” (McCarthy & Zald 1977) and “political translators” (Doerr 2018) in CLI networks: Positionality within structural power relations (Jo 2011); Identity factors (age/generational cohort, gender, cultural narratives): Social space (positioning within structural power relations) only partially overlaps with the “space of lifestyles” (Flemmen et al 2018). Positionality determines access to different forms of capital (financial, social, cultural), influencing choices of frames and strategic linkages, as well as agenda-setting power vis-à-vis institutions.